Pengaturcaraan ingatan setempat di dalam sistem pengoperasian DOS - Romli, Aziz (Penerbit UTM Press, 1990)
Multitasking operating system is a facility in order to execute several applications simultaneously. But not all computers (such as IBM PC) can provide multitasking capability because of hardware limitations. Therefore resident program is the next best solution to overcome multitasking limitation. This paper discussed about the development of resident program with the problems that will be facing and how to solve it.